Clinical experience record book for student nurses - Alfonte, Arminda E. (Manila, Philippines : Merriam & Webster Bookstore, 1986)
The purpose of this Clinical experience Record Book is to provide a guise with Master list of nursing procedures and functions which are necessarily performed by nurses.
Introduction to the use of the experience record book -- Master list of basic nursing procedures -- Surgical nursing diseases and conditions -- Master list if surgical nursing procedures -- Summary of surgical nursing experience -- Medical nursing diseases and conditions -- Master list of medical nursing experience -- Summary of medical nursing experience -- Master list of diseases in pediatrics -- Basic nursing procedures in pediatrics -- Summary of pediatric nursing experience -- Obstetric conditions -- Obstetric nursing procedures -- Summary if obstetrical nursing experience -- Psychiatric nursing procedures -- Summary of psychiatric nursing experience -- List of communicable diseases -- Communicable disease nursing procedures -- Summary of communicable nursing experience -- Urologic nursing procedures -- Orthopedic nursing procedures -- Eye nursing procedures -- Basic nursing procedures in public health -- Ward administration experience record -- Summary of conferences and remarks -- Affiliation clinical experience record -- Student attendance record.
Keywords: NURISNG